Identifikasi Senyawa Antioksidan dari Daun Dewa (Gynura Pseudochina (Lour.) Dc) - Rivai, Harrizul; Bakhtiar, Amri; Nurdin, Hazli; Suyani, Hamzar; Weltasari, Dewi (Jurnal Sains dan Teknologi Farmasi, 2012)
dentification of antioxidative compounds in God leaves [Gynura pseudochina (Lour.) DC] has been performed. The dried leaves were extracted by reflux consecutively with hexane, chloroform and methanol. Each of extract was concentrated using rotary vacuum evaporator. DPPH method was used to examine the antioxidant activity of the extract. The methanolic extract exhibited the strongest antioxidative activity. Then the methanolic extract was isolated by preparative paper chromatography method. The isolated compounds were screened for their antioxidative activity by DPPH method and characterized by chemical and spectroscopic methods. Results indicated that the compound 3â,4â,5,7-tetrahydroxy flavonol (quercetin) was the most active as antioxidant and can be used as marker in standardization of God leaves or its extract.